Hyperreflective Intraretinal Spots in Diabetics without and with Nonproliferative Diabetic Retinopathy: An In Vivo Study Using Spectral Domain OCT - Stela Vujosevic; Silvia Bini; Giulia Midena; Marianna Berton; Elisabetta Pilotto; Edoardo Midena (Journal of Diabetes Research)
Purpose. To evaluate the presence of hyperreflective spots (HRS) in diabetic patients without clinically detectable retinopathy (no DR) or with nonproliferative mild to moderate retinopathy (DR) without macular edema, and compare the results to controls. Methods. 36 subjects were enrolled: 12 with no DR, 12 with DR, and 12 normal subjects who served as controls. All studied subjects underwent full ophthalmologic examination and spectral domain optical coherence tomography (SD-OCT). SD-OCT images were analyzed to measure and localize HRS. Each image was analyzed by two independent, masked examiners. Results. The number of HRS was significantly higher in both diabetics without and with retinopathy versus controls (P<0.05) and in diabetics with retinopathy versus diabetics without retinopathy (P<0.05). The HRS were mainly located in the inner retina layers (inner limiting membrane, ganglion cell layer, and inner nuclear layer). The intraobserver and interobserver agreement was almost perfect (κ> 0.9). Conclusions. SD-OCT hyperreflective spots are present in diabetic eyes even when clinical retinopathy is undetectable. Their number increases with progressing retinopathy. Initially, HRS are mainly located in the inner retina, where the resident microglia is present. With progressing retinopathy, HRS reach the outer retinal layer. HRS may represent a surrogate of microglial activation in diabetic retina.